(untitled) (Pesquisa Odontológica Brasileira, 2002)
The objective of this study was to evaluate the effects of primer and thermocycling on the bond strength of multi-purpose adhesive systems applied to enamel, under tensile stress. The following bonding systems were applied, according to the manufacturers' instructions, on unground enamel buccal surfaces of 96 premolars, with or without the application of primer: Scotchbond MP, OptiBond FL, Amalgambond Plus and OptiBond (dual-cure). A composite resin (Z100, 3M) was applied and light-cured in a cast metal hollow cone, which was previously fixed to the enamel surfaces. Half of the sample was subjected to 3,000 thermocycles (5-37ºC; 37-55ºC, dwell time of 60 s), and the other half was stored in water at 37ºC for the same period. The data were treated by means of ANOVA and no significant effects were detected, which indicates that tensile bond strength was not affected by the adhesive systems, application of primer or thermocycling.